2022
DOI: 10.1371/journal.pgen.1010150
|View full text |Cite|
|
Sign up to set email alerts
|

A modified TurboID approach identifies tissue-specific centriolar components in C. elegans

Abstract: Proximity-dependent labeling approaches such as BioID have been a great boon to studies of protein-protein interactions in the context of cytoskeletal structures such as centrosomes which are poorly amenable to traditional biochemical approaches like immunoprecipitation and tandem affinity purification. Yet, these methods have so far not been applied extensively to invertebrate experimental models such as C. elegans given the long labeling times required for the original promiscuous biotin ligase variant BirA*… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 101 publications
(148 reference statements)
0
14
0
Order By: Relevance
“…It allows efficient bait elution, protects from contamination with ligand–peptides, uses nontoxic, mild chemical conditions, and is simple to carry out. We have adopted the protocol as a standard procedure in our core facility, and it has been successfully used in several projects. , In conclusion, the protocol presented in this study offers a practical and efficient solution for preventing ligand contamination in AP–MS samples with potential applications in a variety of research settings.…”
Section: Discussionmentioning
confidence: 99%
“…It allows efficient bait elution, protects from contamination with ligand–peptides, uses nontoxic, mild chemical conditions, and is simple to carry out. We have adopted the protocol as a standard procedure in our core facility, and it has been successfully used in several projects. , In conclusion, the protocol presented in this study offers a practical and efficient solution for preventing ligand contamination in AP–MS samples with potential applications in a variety of research settings.…”
Section: Discussionmentioning
confidence: 99%
“…This is reminiscent of the region to which Cep135 and Cep97 localize in the fly centriole (34). It has been suggested that a divergent Cep135 protein localizes to centrioles of C. elegans during certain developmental stages (49), and it will be interesting to use U-Ex-STED to address whether it maps to this density. Alternatively, it is possible that a segment of the proteins tested here and localizing to such a density would not be apparent from tagging the N-or C-terminal part of the protein, or with some of the antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpressing a patronin::TurboID fusion protein in the worm gut successfully highlighted the interactome of this microtubule-binding protein (18). Fusing TurboID to an anti-GFP nanobody allowed tissue-specific analysis of the interactomes of the GFP-tagged centrosomal proteins PLK-1 and SPD-5 (19). We identified interactors of the presynaptic active zone protein ELKS-1 by knocking in a TurboID::mNeongreen cassette at the elks-1 locus (10).…”
Section: Introductionmentioning
confidence: 99%